METHODOLOGY OF RESEARCHING THE PROBLEM OF SOCIAL AND PEDAGOGICAL SUPPORT OF MOTHERHOOD AND CHILDREN IN UKRAINE (XX - Beginning of XXI Century) - Stynska, Viktoriia (Mountain School of Ukrainian Carpaty, 2023)
The article is devoted to the methodological basis of the study of socio-pedagogical support for motherhood and childhood, which is revealed at the philosophical, general scientific and specific scientific levels. At the philosophical level (general principles of cognition and the categorical composition of science in general), the principles of dialectics and the principles of development, interdisciplinarity, general connection and determinism in unity with axiological, anthropological, systemic approaches provide an opportunity to determine the philosophical foundations of the unity of the theory and practice of socio-pedagogical support for motherhood and childhood (XX - early XXI centuries). At the level of general scientific methodology (key theoretical provisions, approaches used in most scientific disciplines) - terminological (to correlate the terminological apparatus and the author's interpretation of the basic categories); cultural (to study social, pedagogical, psychological and other phenomena and objects through the prism of the phenomenon of culture); socio-cultural (to study socio-pedagogical support for motherhood and childhood in the interdisciplinary space); Innovative (to implement the experience of establishing social and pedagogical support for motherhood and childhood in order to maximize the use of the positive achievements of the past at the present stage). At the level of a specific scientific methodology (a set of paradigms, theories of social pedagogy, approaches, principles implemented in scientific research) - paradigms (personal, personal-social); theories (socialization (cyclic, socializationeventualization, factor)), social capital, status-role), approaches (personal-social-activity, environmental, ethical, behaviorist, psychoanalytic, maternal-centered, child-centered, family-centered, historical and pedagogical, narrative, chronological and the principle of diachrony. It is concluded that the use of the above methodological approaches will help to consider at the theoretical and practical level and objectively reproduce and outline the conceptual vectors of the studied problem of socio-pedagogical support for motherhood and childhood.